Active Damping of Thin Film Shape Memory Alloy Devices - Ahmadi, Shahabeddin; Jacob, Kiran; Wendler, Frank; Padhy, Asutosh; Kohl, Manfred (Proceedings in Applied Mathematics and Mechanics, 2021)
The thermomechanical coupling in shape memory alloys (SMAs) provides an effective mechanism of vibration damping by a cyclic structural phase transition. Here, we present simulations for an active SMA damper device based on a polycrystalline film materials, in which active damping via the one-way shape memory effect is exploited. We apply an extension of a previously reported superelastic model, that combines transition state kinetics with a phase field approach for the case of shock loading. By this approach, we are able to describe the time-resolved active damping performance of the device in agreement with experimental results.<br